Nonlocal and nonlinear diffusions and interactions : new methods and directions : Cetraro, Italy 2016 /: new methods and directions : Cetraro, Italy 2016. (2017) - Carrillo, José Antonio, 1969-; (Professor), Pino, Manuel del; Figalli, Alessio, 1984-; Mingione, Giuseppe, 1972-; Vazquez, J. L (Juan Luis)
No abstract available